2021
DOI: 10.31635/ccschem.020.202000250
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide-Containing Molecular Sticker Assists Cellular Delivery of DNA Nanoassemblies by Bypassing Endocytosis

Abstract: The delivery efficiency of DNA nanoassemblies to the cytosol remains unsatisfactory due to endoand lysosomal entrapment and degradation, which restricts their bioanalytical and biomedical applications. Herein, the authors developed a disulfide-containing molecular sticker (DSMS) assisted approach to achieve efficient cytosolic delivery of DNA nanoassemblies. DSMS is designed to consist of a disulfide unit for thiol-mediated uptake and a guanidinium cation unit for strongly adhering to DNA nanoassemblies. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Recently, a similar salt bridge strategy was further exploited for the delivery of DNA. 149 Ping et al recently reported a series of CPDs by exploring mechanisms to universally deliver different forms of CRISPR-Cas9 components, including Cas9 plasmid, sgRNA, Cas9 mRNA, and Cas9 ribonucleoprotein (RNP). After screening, DET-CPD-12 with diethylenetriamine (DET) and CPD blocks was utilized for in vivo delivery of CRISPR-Cas9 targeting CCNE1 to successfully prevent fulminant hepatic failure (FHF).…”
Section: Biomacromolecular Drugsmentioning
confidence: 99%
“…Recently, a similar salt bridge strategy was further exploited for the delivery of DNA. 149 Ping et al recently reported a series of CPDs by exploring mechanisms to universally deliver different forms of CRISPR-Cas9 components, including Cas9 plasmid, sgRNA, Cas9 mRNA, and Cas9 ribonucleoprotein (RNP). After screening, DET-CPD-12 with diethylenetriamine (DET) and CPD blocks was utilized for in vivo delivery of CRISPR-Cas9 targeting CCNE1 to successfully prevent fulminant hepatic failure (FHF).…”
Section: Biomacromolecular Drugsmentioning
confidence: 99%
“…The assembly and disassembly processes were controlled by the addition of peroxide and GSH, respectively, which could be used as a stimulus-responsive cargo delivery system. Creation of a disulfide-containing molecular sticker (DSMS) on a DNA nanostructure was reported to aid in cellular uptake . DSMS was attached to the DNA nanostructures through salt bridges formed by the cationic guanidinium groups, and the disulfide-containing tail helped in direct delivery to cells.…”
Section: Nucleic Acid Carriers With Disulfide-sensitive Functionalitiesmentioning
confidence: 99%
“…Creation of a disulfide-containing molecular sticker (DSMS) on a DNA nanostructure was reported to aid in cellular uptake. 211 DSMS was attached to the DNA nanostructures through salt bridges formed by the cationic guanidinium groups, and the disulfide-containing tail helped in direct delivery to cells.…”
mentioning
confidence: 99%
“…Besides the abovementioned surface modification by peptides, a disulfide-containing molecular sticker (DSMS) was reported to be utilized to assist the cellular delivery of DNA nanostructures. [41] Consisted of guanidinium cation units, DSMS can strongly adhere to phosphate groups of DNA structures via multiple salt bridges. The characterization results showed that the [29] Copyright 2020, Nature Publishing Group.…”
Section: Cellular Functional Regulation and Therapeutic Effects On The Cell Surfacementioning
confidence: 99%